Protective effect of pinostrobin against gentamicin-induced toxicity in human renal proximal tubular cells - Lawan Siangjong; Paranee Meetam (Pensoft Publishers, 2024)
Pinostrobin, an active ingredient found in aromatic rhizoids of the Zingiberaceae family, has shown several pharmacological activities, including anti-inflammation and anti-oxidation. This study aimed to investigate the potential of pinostrobin to prevent the toxicity of renal tubular cells caused by gentamicin. Gentamicin causes a decrease in the cell viability of human renal proximal tubule cells (RPTEC/TERT1) in a concentration-dependent manner. Our findings showed that pre-incubation with pinostrobin significantly attenuated the toxicity induced by gentamicin in RPTEC/TERT1 cells. The mechanism underlying the nephroprotective effect of pinostrobin was investigated. The protein expression of TIM-1, a kidney injury marker, was increased upon gentamicin treatment and was diminished by pinostrobin co-administration. In addition, we also showed that after 48 h of incubation, pinostrobin inhibited the uptake of OCT1 and OCT2 substrate (3H-MPP+) in CHO-K1 cells, overexpressing human OCTs, suggesting a possible mechanism of pinostrobin interfering with gentamicin accumulation in renal proximal tubule cells where OCTs were highly expressed. In summary, administering pinostrobin prior to gentamicin exposure could potentially reduce the nephrotoxicity caused by gentamicin.